2012
DOI: 10.1103/physrevlett.109.242002
|View full text |Cite
|
Sign up to set email alerts
|

Gluon- and Quark-Jet Multiplicities with NNNLO and NNLL Accuracy

Abstract: We present a new approach to consider and include both the perturbative and the nonperturbative contributions to the multiplicities of gluon and quark jets. Thanks to this new method, we have included for the first time new contributions to these quantities obtaining next-to-next-to-leading-logarithmic resummed formulas. Our analytic expressions depend on two nonperturbative parameters with a clear and simple physical interpretation. A global fit of these two quantities shows how our results solve a long-stand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 29 publications
6
45
0
Order By: Relevance
“…mean multiplicities of quarks and gluons) were analyzed [32]. The results are in good agreement with the experimental data (see contribution [33] by Paolo Bolzoni to this Proceedings).…”
Section: Parton Distributions and The Structure Function Fsupporting
confidence: 72%
“…mean multiplicities of quarks and gluons) were analyzed [32]. The results are in good agreement with the experimental data (see contribution [33] by Paolo Bolzoni to this Proceedings).…”
Section: Parton Distributions and The Structure Function Fsupporting
confidence: 72%
“…Moreover, using an analogous approach, good agreement was also found with the corresponding data for jet multiplicites[30] 4. The study of nuclear effects in a deutron can be found in the recent paper[31], which also contains short reviews of preliminary investigations.…”
supporting
confidence: 68%
“…Using a recent progress in the application of double logarithmic approximations (see [15,20] and [30]) to the studies of small x behavior of the structure and fragmentation functions, 5 Note that the result for R AD g (x, µ 2 ) along with its uncertainty is completely determined by both the rescaling model and the analytic form for parton densities at low x values we've used. Therefore, it is clear that the light green band for R AD g (x, µ 2 ) should become broader due to a freedom in using various models.…”
Section: Resultsmentioning
confidence: 99%
“…The number of jet constituents scales up logarithmically with decreasing energy scale (see e.g. [158,159]), as does the entropy of a jet [160], and both of these quantities are related to the effective dimensionality of the space of QCD jets. We leave a QCD calculation of dim(Q) to future work, noting that the result will depend on the strong coupling constant α s as well as on the relative fraction of quark and gluon jets in the sample.…”
Section: Correlation Dimensionmentioning
confidence: 99%